Prakiraan Usia Gigi Menggunakan Standar Blenkin (Modifikasi Metode Demirjian) pada Anak-Anak Etnik Jawa di Kabupaten Jember - Dwi Kartika Apriyono (Fakultas Kedokteran Gigi Universitas Jember, 2020)
Chronological and dental age are necessary aspects of dental age estimation. Both have a close relationship. Chronological age reflects the age of the tooth, and vice versa. Dental age estimation aims to provide the data in the field of dentistry with an accurate dental age range. In order to get the value of an accurate estimate of dental age, needed a method of estimation that has a standard deviation as low as possible and validated in a specific population groups of an individual. Demirjian method is a method frequently used in the dental age estimation. It uses the classification stages of the seven permanent teeth of mandibular left side using panoramic radiographs. Application of its method in some countries showed vary results so it needed adjustment. Blenkin standard is an adjustment of its method that changes the score of maturity stages 0-H to 1-8 and calculate the dental age by regression formula. The study aimed to assess the dental age estimation using Blenkin standard on children of Javanese ethnic in Jember region. This was an analytic descriptive study design. The samples were panoramic radiographs. The subjects were 70 samples consisting of 29 boys and 41 girls with an age range 6-12 years, and they were divided into 7 groups based on chronological age. Each tooth of the sample was calculated using Blenkin standard. The Blenkin standard showed non-significant difference with the age difference in the amount of approximately -0.22 years for boys and -0.03 years for girls (underestimation).